2011
DOI: 10.1177/0734242x10397968
|View full text |Cite
|
Sign up to set email alerts
|

Sources of microbial pathogens in municipal solid waste landfills in the United States of America

Abstract: Municipal solid waste (MSW) categories, as specified by United States Environmental Protection Agency (US EPA), were evaluated for their relative contribution of pathogenic viruses, bacteria, and protozoan parasites into MSW landfills from 1960 to 2007. The purpose of this study was to identify trends and quantify the potential contribution of pathogens in MSW as an aid to the assessment of potential public health risks. A review of the literature was conducted to estimate values for the concentrations of faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 25 publications
1
22
0
4
Order By: Relevance
“…The majority of protozoan parasites (97%) are expected to come from pet feces; however, the evidence suggests that enteric protozoa would be expected to be inactivated by temperatures above 45°C and that most landfills achieve temperatures of 38°C to 78°C (143). There is still much uncertainty about the survival of enteric protozoa in leachate from unlined landfills and the resultant contamination of underground aquifers and the water supply.…”
Section: Waterborne Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of protozoan parasites (97%) are expected to come from pet feces; however, the evidence suggests that enteric protozoa would be expected to be inactivated by temperatures above 45°C and that most landfills achieve temperatures of 38°C to 78°C (143). There is still much uncertainty about the survival of enteric protozoa in leachate from unlined landfills and the resultant contamination of underground aquifers and the water supply.…”
Section: Waterborne Transmissionmentioning
confidence: 99%
“…There is still much uncertainty about the survival of enteric protozoa in leachate from unlined landfills and the resultant contamination of underground aquifers and the water supply. One of the most recent studies to evaluate this found the presence of viable Giardia in large concentrations in leachate (143).…”
Section: Waterborne Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…they are not infectious for healthy people. However, a few are real pathogens, such as Legionella species (Conza et al, 2013;Currie et al, 2014) or enteric pathogens in pet excrements and disposable diapers (Gerba et al, 1995(Gerba et al, , 2011. Some airborne microorganisms (mainly fungi, such as Aspergillus fumigatus and Zygomycetes species) may act as opportunists in fragile people, that are immunocompromised or present lung damages often associated with prescription of steroids (Cornillet et al, 2006;Latgé, 1999;Roden et al, 2005).…”
Section: What Do We Know About Bioaerosol-related Risk For Waste Workmentioning
confidence: 99%
“…Graczyk et al (2008) e Cheng et al (2009) relataram, respectivamente, 27 e 9 cistos de Giardia por grama de lodo. Gerba et al (2011) relataram variação no número de cistos de 10 a 1000 cistos por grama.…”
Section: Okojokwu Et Al (2014)unclassified